Low-cost treatment method for organic matter and nutrients in landfill leachate - G. R. Y. Perera; W. K. C. Neetha Dayanthi (IWA Publishing, 2023)
In this study, the ability of low-cost composite adsorbents to treat organic compounds in terms of chemical oxygen demand (COD), total nitrogen (TN), and total phosphorus (TP) was investigated. The composite adsorbents were composed of washed sea sand (WSS), dewatered alum sludge (DAS), zero-valent iron (ZVI), and granular activated carbon (GAC). The removal efficiency of COD in landfill leachate by a composite adsorbent (composed of WSS (40%), DAS (40%), ZVI (10%), and GAC (10%) in weight) was 79.93 ± 1.95%. The corresponding adsorption capacity was 8.5 mg/g. During batch sorption experiments, the maximum COD removal efficiencies given by DAS, WSS, ZVI, and GAC were 16, 51.3, 42, and 100.0%, respectively. The maximum removal efficiencies of the above composite adsorbent for TN and TP were 84.9 and 97.4%, respectively, and the adsorption capacities were 1.85 and 0.55 mg/g, respectively. The Elovich isotherm model gave the best fit for COD, TN, and TP adsorption. This composite adsorbent can treat more than one contaminant simultaneously. The application of DAS and ZVI to make an efficient adsorbent for wastewater treatment would be a good re-use application for them, which would otherwise be landfilled directly after their generation. HIGHLIGHTS This investigates the applicability of composite adsorbents made of low-cost/waste materials, in landfill leachate treatment.; The composite adsorbent has considerable treatment potential.; This can be an initial study leading to further studies.; The use of waste materials makes treatment economically and practically feasible.; This is also a sustainable re-use application for the waste to be dumped.;